2016
DOI: 10.1021/acs.jpcc.6b10417
|View full text |Cite
|
Sign up to set email alerts
|

Surface Magnetism of Cobalt-Doped Anatase TiO2 Nanopowders

Abstract: Cobalt-doped anatase Ti1–x Co x O2 (0 < x ≤ 0.04) nanopowders (with a particle size of 30–40 nm) were produced by the hydrothermal synthesis method. Morphology, structure, and thermal stability of the synthesized compounds were examined using transmission electron microscopy, infrared spectroscopy, and X-ray diffraction analysis. Using X-ray photoelectron spectroscopy, cobalt ions are shown to have an oxidation state of 2+, with titanium ions having a tetravalent state of Ti4+. In the as-prepared state, all in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Among various transition metals (i.e., Pt, Ag, Au, Ru, and Pd) [28][29][30][31] and transition metal oxides (i.e., Cu 2 O, α-Fe 2 O 3 ) [32][33][34], cobalt [35,36] and cobalt oxides [37][38][39][40] as an interesting low-cost and earth-abundant mineral have attracted tremendous attention for the development of visible light active TiO 2 materials. Cobalt-doped TiO 2 photocatalysts have been synthesized by various methods, such as the sol/gel technique [36,[41][42][43][44][45][46][47][48][49][50], hydrothermal treatment [51][52][53][54], impregnation method [55,56], precipitation process [57] for the photocatalytic degradation of methylene blue [57,58], rhodamine B [58], methylene orange [57], phenol [41], 2-chlorophenol [41], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various transition metals (i.e., Pt, Ag, Au, Ru, and Pd) [28][29][30][31] and transition metal oxides (i.e., Cu 2 O, α-Fe 2 O 3 ) [32][33][34], cobalt [35,36] and cobalt oxides [37][38][39][40] as an interesting low-cost and earth-abundant mineral have attracted tremendous attention for the development of visible light active TiO 2 materials. Cobalt-doped TiO 2 photocatalysts have been synthesized by various methods, such as the sol/gel technique [36,[41][42][43][44][45][46][47][48][49][50], hydrothermal treatment [51][52][53][54], impregnation method [55,56], precipitation process [57] for the photocatalytic degradation of methylene blue [57,58], rhodamine B [58], methylene orange [57], phenol [41], 2-chlorophenol [41], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other scientific groups reported that cobalt-modified TiO 2 synthesized by wet impregnation methods seems to increase the photocatalytic activity [55,56]. Additionally, earlier studies have been mostly done on Co-doped TiO 2 thin films, and the main focus has commonly been made on the ferromagnetic properties of these catalysts [45,53,[62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…The positive shift of Ti 2p1/2 and Ti 2p3/2 peaks of TP-TiO2 were observed in the Ti 2p XPS spectra (Figure 2a). The shift in Ti 2p can be attributed to the ameliorated surface states [32,33]. This positive shift of Ti 2p demonstrates that the Ti-O-P-O bonds were successfully formed on the surface of the TiO2 core particle, and resulted in the reduction of trap states originated from Ti 3+ defects.…”
Section: Chemical Modificationmentioning
confidence: 88%
“…1d). 33,34 No other crystal was found in the HRTEM image of PCNT(S)-2, indicating that Co 3 O 4 were probably dispersed in the N-TiO 2 particles rather than loaded onto the surface of N-TiO 2 . No Pt particle was found in either sample, suggesting the low content of Pt in the composites.…”
Section: Morphologies and Structuresmentioning
confidence: 99%